2012
DOI: 10.1016/j.bbmt.2012.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Unrelated Donor Cord Blood Transplantation for Children with Severe Sickle Cell Disease: Results of One Cohort from the Phase II Study from the Blood and Marrow Transplant Clinical Trials Network (BMT CTN)

Abstract: The Sickle Cell Unrelated donor Transplant trial (SCURT trial) of the Blood and Marrow Transplant Clinical Trials Network (BMT CTN) is a phase II study of the toxicity and efficacy of unrelated donor hematopoietic cell transplantation in children with severe sickle cell disease (SCD) using a reduced intensity conditioning regimen. Here we report the results for the cord blood cohort of this trial. Eight children with severe SCD underwent unrelated donor cord blood transplantation (CBT) following alemtuzumab, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
152
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 181 publications
(160 citation statements)
references
References 40 publications
5
152
0
1
Order By: Relevance
“…Analyses showed that OS, DFS, acute and chronic GvHD were 95%, 88%, 20%, and 12%, respectively for BM recipients (n=389), and 96%, 81%, 10%, and 5%, respectively for CB recipients (n=70). In this cohort, the cell dose (median 3.9x10 7 /kg) did not influence outcome of patients given cord blood. 21 …”
mentioning
confidence: 70%
See 3 more Smart Citations
“…Analyses showed that OS, DFS, acute and chronic GvHD were 95%, 88%, 20%, and 12%, respectively for BM recipients (n=389), and 96%, 81%, 10%, and 5%, respectively for CB recipients (n=70). In this cohort, the cell dose (median 3.9x10 7 /kg) did not influence outcome of patients given cord blood. 21 …”
mentioning
confidence: 70%
“…So far, a total of 32 patients with SCD transplanted with an UCB unit have been published, 18 of them following an RIC regimen, with an overall survival of 91%, but a diseasefree survival of only 50% because of rejection. 7,45,83,84 The Sickle Cell Unrelated Donor Transplant Trial (SCURT trial) of the Blood and Marrow Transplant Clinical Trials Network (BMT CTN) was a phase II study on the toxicity and efficacy of UCB or BMT in children with severe SCD using RIC. Eight children with severe SCD underwent unrelated donor CB-transplantation following alemtuzumab, fludarabine, and melphalan.…”
Section: Alternative Donor Transplantationmentioning
confidence: 99%
See 2 more Smart Citations
“…Transplantation of allogeneic cells carries the risk of graft-versushost disease (GvHD), which can be a cause of extensive morbidity. HSCT using UCB from matched unrelated donors holds reduced risk of acute or chronic GvHD compared with using BM; however, there is a higher probability of engraftment failure using UCB as a result of its lower cell dose and immunologic immaturity (8,9).…”
Section: Introductionmentioning
confidence: 99%